Reciprocidade e ação coletiva entre agricultores familiares no Pará - SCHMITZ, Heribert (Museu Paraense Emílio Goeldi, 2022)
The aim of this article is to analyze the persistence of collective action in the community Santa Ana, Mãe do Rio, Pará State, Brazil. The analytical framework is part of the debate on the motivation for people to engage voluntarily in collective action. In this article, the relationships of reciprocity to collective action undertaken within the scope of the peasants’ organizations are addressed. The methodology consisted of a case study, with collection of secondary data, observations of cooperative events realized by the groups and interviews with residents and leaders. The results demonstrate that collective action takes different shapes, depending on the existence of reciprocal relationships among the participants of these organizations in Santa Ana.